Horizon - La Fontaine, Christopher ([Princeton, NJ : Films for the Humanities & Sciences, 1998)
'Horizon' traces the life of John Maynard Keynes through the eyes of some of the people who knew him. This programme also spells out some of his policies which were in direct opposition to the monetarist policies of the Thatcher administration. Keynes was more than a theoretical economist, he believed that there should be a moral basis to economics and that the state had a duty to patronise the arts
Title from title screen
Narrator: Paul Vaughan
DVD Format
Keywords: Keynes, John Maynard, -- 1883-1946; Economic conditions; World War, 1914-1918 -- Economic aspects; Unemployment